Effect of Static and Dynamic Quadriceps Exercise Program on Pain Reduction in Knee Osteoartrose Patients in Dempo Surgery - Wiek Israwan; Nurwijayanti (Journal for Quality in Public Health, 2022)
Osteoarthritis is a degenerative disease of the joints that involves cartilage, joint lining, ligaments, and bones, causing pain and stiffness in the joints. This study aims to explain the effect of the Static and Dynamic Quadriceps Exercise Program on reducing pain in Knee Osteoartrose Patients at Dempo Surgery. This study is a quantitative using a quasi-experimental design with a two groups pretest-posttest approach with control group design, namely by adding a comparison group where the first group, namely the treatment group, was given static quadriceps exercise and the second group, namely the control group with dynamic quadriceps exercise and taking medication that is provided by the health center. The structure of the research design contains 3 components, namely the initial state, the treatment and the condition due to the treatment. This study involved 28 samples were determined by total sampling technique because the number of respondents was not so large that the results were expected to be more valid. Collecting data on signs and symptoms of knee osteoarthritis which includes knee joint pain was measured by VAS. The data that has been collected is then processed and analyzed using the SPSS program. Before analyzing the data, the researcher conducted a Classical Assumption test by testing homogeneity and normality. The test results show that the data collected is normally distributed and homogeneous. The results of hypothesis testing indicate that there is an effect of the Static and Dynamic Quadriceps Exercise Program on reducing pain in Knee Osteoartrose Patients at Dempo Surgery.